The control of professional interests of young workers - Čebelis, J. (Psichologija, 1988)
The present paper describes the methods and results of the control of professional interests of young workers at the Vilnius Furniture Combine. The necessity to differentiate the stimuli and the mechanism of control of professional interests of young workers is shown. The dependence of differentiation on the level of the already formed professional interests is revealed. The exploratory results show that it is possible to raise the level of professional interests among young workers, this leading to the improvement of production indices and the reduction in manpower fluctuation. The control of professional interests of young workers proves to be effective and the methods used are recommended for many enterprises.
Keywords: young workers; professional interests